2018
DOI: 10.1001/jamaophthalmol.2018.0786
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Description of Reliable Evidence for 2016 American Academy of Ophthalmology Preferred Practice Pattern Guidelines for Cataract in the Adult Eye

Abstract: IMPORTANCETrustworthy clinical practice guidelines require reliable systematic reviews of the evidence to support recommendations. Since 2016, the American Academy of Ophthalmology (AAO) has partnered with Cochrane Eyes and Vision US Satellite to update their guidelines, the Preferred Practice Patterns (PPP).OBJECTIVE To describe experiences and findings related to identifying reliable systematic reviews that support topics likely to be addressed in the 2016 update of the 2011 AAO PPP guidelines on cataract in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 106 publications
1
44
0
Order By: Relevance
“…5,[13][14][15] Recruiting and training these authors in Cochrane methods would greatly increase the capacity of Cochrane Eyes and Vision research output and the geographic diversity and representation in Cochrane reviews, as well as improve the overall quality of the evidence for eyes and vision conditions. [6][7][8][9] With regard to gender, we found that both Cochrane and non-Cochrane reviews in the field of eye and vision research had approximately equal representation of gender among first authors who were also the corresponding authors, but that non-Cochrane reviews were less likely to have women than men among authors who had a single role as either first or corresponding author. Our sensitivity analyses There is a substantial amount of literature to support that women are underrepresented in leadership positions in academia.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…5,[13][14][15] Recruiting and training these authors in Cochrane methods would greatly increase the capacity of Cochrane Eyes and Vision research output and the geographic diversity and representation in Cochrane reviews, as well as improve the overall quality of the evidence for eyes and vision conditions. [6][7][8][9] With regard to gender, we found that both Cochrane and non-Cochrane reviews in the field of eye and vision research had approximately equal representation of gender among first authors who were also the corresponding authors, but that non-Cochrane reviews were less likely to have women than men among authors who had a single role as either first or corresponding author. Our sensitivity analyses There is a substantial amount of literature to support that women are underrepresented in leadership positions in academia.…”
Section: Discussionmentioning
confidence: 84%
“…5 Details of the generation of this database and its use are reported elsewhere. [6][7][8][9] We selected all Cochrane reviews in the database (n = 313) and randomly selected 313 non-Cochrane intervention reviews from the remaining records in the database. The 313 non-Cochrane reviews were selected using Microsoft Excel's random number function to assign each record a unique identifier and then ordering all records, then selecting the first 313 intervention reviews.…”
Section: Sample Selectionmentioning
confidence: 99%
“…14,[27][28][29] Recruiting and training these authors in Cochrane methods would greatly increase the capacity of Cochrane Eyes and Vision research output and the geographic diversity and representation in Cochrane reviews, as well as improve the overall quality of the evidence for eyes and vision conditions. [15][16][17][18] This research is not without limitations, primarily in the method of ascertaining gender and the restriction to rst and corresponding author positions. We used an algorithm which we had previously developed and tested to ascertain the gender of included authors.…”
Section: Discussionmentioning
confidence: 99%
“…14 Details of the generation of this database and its use are reported elsewhere. [15][16][17][18] We selected all Cochrane reviews of intervention in the database (n = 313) and randomly selected 313 non-Cochrane intervention reviews from the remaining 4,138 records in the database. We selected the 313 non-Cochrane reviews by assigning each record a randomly-generated, unique identi er and selected the rst 313 intervention reviews.…”
Section: Sample Selectionmentioning
confidence: 99%
“…We used a database of 4451 systematic reviews in eyes and vision maintained by the Cochrane Eyes and Vision US Satellite (CEV@US) [14]. Details of the generation of this database and its use are reported elsewhere [15][16][17][18]. We selected all Cochrane reviews of intervention in the database (n = 313) and randomly selected 313 non-Cochrane intervention reviews from the remaining 4138 records in the database.…”
Section: Sample Selectionmentioning
confidence: 99%